THE ROLES OF THE PUBLIC SECTOR AND THE PRIVATE SECTOR IN THE ECONOMY OF NORTH CYPRUS: EMPIRICAL EVIDENCE FROM MARKOV SWITCHING - TURSOY, Turgut (Theoretical and Practical Research in Economic Fields; Vol 9 No 2 (2018): TPREF, Volume IX, Issue 2(18), Winter 2018, 2018)
This study purpose is to examine the regime shift of public sector and private sector investments on economic growth in North Cyprus using with the Markov Switching Regression technique for the period from the first quarter of the year 1982 to the last quarter of the year of 2015. Both sector investments having effects on the economic growth at the concerned period and method provide the necessary evidence for the regime shifts. Two-regime (growth path/recession path) model has been estimated to analyse the Markov-switching model, Markov transition probabilities and constant expected durations.